1990
DOI: 10.1148/radiology.176.3.2389038
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic imaging of patients with intracranial tumors: H-1 MR spectroscopic imaging and PET.

Abstract: Hydrogen-1 magnetic resonance (MR) spectroscopic images of patients with intracranial tumors were obtained. Metabolite maps of N-acetyl aspartate, choline, lactate, and creatine concentrations were reconstructed with a nominal spatial resolution of 7 mm and a section thickness of 25 mm. The metabolite maps showed variations in metabolite concentrations across the tumor. In one patient, it was observed that choline concentration was increased in one part of the tumor but decreased in another part. In another pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(81 citation statements)
references
References 0 publications
4
75
1
1
Order By: Relevance
“…In previous studies it was hypothesized that malignant tumours have a high metabolic rate (41). Additionally, some reports showed correlation between glucose consumption rate and lactate levels for gliomas, suggesting alterations in glycolysis in brain tumours (42). However, we did not find a statistically significant correlation between lactate levels and tumour grade.…”
Section: Resultscontrasting
confidence: 81%
“…In previous studies it was hypothesized that malignant tumours have a high metabolic rate (41). Additionally, some reports showed correlation between glucose consumption rate and lactate levels for gliomas, suggesting alterations in glycolysis in brain tumours (42). However, we did not find a statistically significant correlation between lactate levels and tumour grade.…”
Section: Resultscontrasting
confidence: 81%
“…The use of the Cho/Cr ratio in the evaluation of neoplastic lesions has already been described in the literature as Cho is an important constitute of cell membranes with increases occurring when there are increases in cell synthesis and conversion to carcinogenic cells, while creatine is generally stable 8,9 . NAA is found in normal neurons and when altered, reductions occur both in tumors and in inflammatory lesions thereby indicating neuronal loss.…”
Section: Discussionmentioning
confidence: 99%
“…Using arguments similar to those of Eqs. [2] and [4], they found that the SNRs of the two methods were indistinguishable when the TRs were the same, or when the TR was Ͻ T 1 and an Ernst angle was used. While both conditions can be met in MRI, where T C Ͻ Ͻ T 1 , neither is practical in MRS in general, especially for 3D 1 H-MRS.…”
Section: Fig 4 Topmentioning
confidence: 99%
“…This technique (see Fig. 1a), which is known as MRS imaging (MRSI) and was first described for 1 H by Luyten et al (4), yields much more spatial information at equal SNR (5), as determined by the voxel size and acquisition time (6). To reduce SNR loss from incomplete longitudinal relaxation, T 1 , the TR is extended beyond the actual acquisition-cycle, T C , the time needed to prepare and acquire one transient, as determined primarily by the desired spectral resolution.…”
mentioning
confidence: 99%